1996
DOI: 10.1523/jneurosci.16-22-07308.1996
|View full text |Cite
|
Sign up to set email alerts
|

An Explanation for Reflex Blink Hyperexcitability in Parkinson’s Disease. I. Superior Colliculus

Abstract: Hyperexcitable reflex blinks are a cardinal sign of Parkinson's disease. We investigated the neural circuit through which a loss of dopamine in the substantia nigra pars compacta (SNc) leads to increased reflex blink excitability. Through its inhibitory inputs to the thalamus, the basal ganglia could modulate the brainstem reflex blink circuits via descending cortical projections. Alternatively, with its inhibitory input to the superior colliculus, the basal ganglia could regulate brainstem reflex blink circui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
100
2
4

Year Published

1997
1997
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 177 publications
(120 citation statements)
references
References 40 publications
14
100
2
4
Order By: Relevance
“…For example, a low blinking rate suggests direct inhibition of the central pattern generators, whereas increased excitability of the blink refl ex and Meyerson's sign might be caused by SNr overinhibition of the superior colliculus and secondary disinhibition of the nucleus gigantocellularis. 33 Brainstem mechanisms are also likely to be engaged in the origin of postural disturbances and other motor signs such as dysphagia and dysarthria; however, these features typically occur later in the disease. Bradykinesia can be understood as a failure of neuronal recruitment or "energisation".…”
Section: Motor Features Akinesiamentioning
confidence: 99%
“…For example, a low blinking rate suggests direct inhibition of the central pattern generators, whereas increased excitability of the blink refl ex and Meyerson's sign might be caused by SNr overinhibition of the superior colliculus and secondary disinhibition of the nucleus gigantocellularis. 33 Brainstem mechanisms are also likely to be engaged in the origin of postural disturbances and other motor signs such as dysphagia and dysarthria; however, these features typically occur later in the disease. Bradykinesia can be understood as a failure of neuronal recruitment or "energisation".…”
Section: Motor Features Akinesiamentioning
confidence: 99%
“…In all mammalian species tested, the OOemg response to the second of two identical stimuli was less than that to the first stimulus for short interstimulus intervals Basso et al 1996;Powers et al 1997). With these paired corneal stimuli, Purkinje cells exhibited a complex spike in response to the first stimulus, but no complex spike or burst of simple spike discharge in response to the second stimulus ( Fig.…”
Section: Data Collection and Analysismentioning
confidence: 91%
“…The details of the procedures used in this study have been reported in previous studies (Evinger et al 1993;Basso et al 1996). The animals were prepared for recording electromyograph (EMG) activity of the lid closing, orbicularis oculi muscle (OOemg) and single-unit, extracellular recording.…”
Section: Methodsmentioning
confidence: 99%
“…The increased spontaneous blink rate may result from the increased excitability of the trigeminal system which is dependent on the basal ganglia (83,84). It seems that reduction in dopamine induces a reduction in nucleus raphe magnus activity via the subtantia nigra pars reticulata and superior colliculus (85,86). Schicatano and collegues created a two component model of benign blepharospasm based on the combination of a permissive condition (dopamine depletion) and a precipitating event (corneal irritation and dry eye caused by partial lesion of the zygomatic branch of the facial nerve).…”
Section: Lessons From Rodent Models Of Dystonia: the Genetic Approachmentioning
confidence: 99%